PENGARUH IKLAN NEUROMARKETING TERHADAP PERILAKU COMPULSIVE BUYING DI KALANGAN REMAJA PUTRI PADA PRODUK SKIN CARE CAMILLE BEAUTY - Prana Hardayu, Audisty (Jurnal Ekonomi STIEP, 2023)
The rise of Compulsive buying among consumers has prompted a large number of studies related to this behavior. Adolescents. However, the focus of this study highlights one of the external triggers that may stimulate CB, namely advertising using the new marketing concept of Neuromarketing. This study uses a type of quantitative research with the method Data collection was carried out using a questionnaire distributed by Google Form. The participants were young women aged 13-16 who currently use Camille Beauty skin care products. This study provides evidence that advertisements that use Neuromarketing effects can lead to Compulsive buying. To find out how the concept of Neuromarketing works on advertising in Compulsive buying is to emphasize "The Importance of Eye Gaze" in product advertisements by displaying attractive packaging, colors that match consumer segmentation, puns, anchoring effects and memorable audiotory. Keywords: Advertising, Compulsive buying and Neuromarketing